Avaliação de fatores clínicos, craniofaciais e genéticos associados a DTM dolorosa em pacientes perfil II - Uetanabaro, Lucas Caetano (2019)
The aim of this study was to evaluate factors that may predispose myofascial and/or joint pain in profile II individuals. The research consists of a cross-sectional study with a sample of 65 patients with profile II. For the diagnosis and classification of myofascial and/or joint pain, the RDC /TMD (Research Diagnostic Criteria for Temporomandibular Disorder) was used. The predisposing variables assessed for the association with joint and myofascial pain were sex, joint disc displacement, chronic pain and depression. Craniofacial measurements were obtained using lateral radiographic radiography. To correlate with myofascial pain, linear and angular measures were analyzed and, for joint pain, only angular measures. In addition, cells were collected to acquire DNA by scraping the oral mucosa and genotyping by real-time PCR. The dopamine receptor polymorphisms DRD2 (rs6275 and rs6276) and ANKK1 (rs1800497), were used for the analysis of myofascial pain and, the estrogen receptor polymorphisms ESR1 (rs2234693 and rs9340799), ESR2 (rs1256049 and rs4986938) and IL6 rs1800795 and rs1800796), for the analysis of joint pain. The data obtained were submitted to statistical analysis with a confidence level of 0.05. Myofascial pain was associated with disc displacement on the right side (p <0.001), joint pain (p = 0.043), chronic pain (p = 0.002) and severe depression (p = 0.021). Joint pain was associated with unrestricted disc displacement and chronic pain on both sides (p <0.05). Only on the left side, joint pain was associated with myofascial pain (p = 0.030). In the cephalometric analysis, myofascial pain was associated with the goniac angle of the mandible (p = 0.042) and joint pain was associated with Ricketts facial axis (p = 0.004). In the genetic analysis, myofascial pain was associated with the polymorphisms rs6275 and rs6276 (p <0.05) of the DRD2 gene. For joint pain, there was an association with the rs1256049 and rs4986938 polymorphisms of the ESR2 gene on the right side, and for rs4986938 polymorphism there was an association between the left side joint pain. There was no association between IL6 and joint pain. Thus, it can be concluded that the factors predisposing to myofascial pain are dislocation of the articular disk, chronic pain, depression, decreased goniac angle and polymorphisms of the DRD2 gene. Finally, we can cite as predisposing factors and related to joint pain: myofascial pain, disc displacement without reduction, chronic pain, shortening of Ricketts facial axis and polymorphisms of the ESR2 gene.